THE EU-RUSSIA CONCEPTUAL INTERACTION IN THE EURASIAN SPACE IN THE CONTEXT OF WESTERN SANCTIONS - KORZHENGULOVA, Asia; SHKVARYA, Lyudmila; MELANYINA, Maria (CENTRAL ASIA AND THE CAUCASUS, 2017)
For over twenty-five years, Russia's foreign policy has been a pivotal force in shaping international relations across the post-Soviet space. This policy has evolved in response to both Western political and economic sanctions and internal dynamics. The changing landscape of Russia's interactions in this region reflects various stages of its foreign policy, influenced by both domestic growth and international pressures. As Russia's state power and economic stability have increased, its ability to navigate and exert influence in the post-Soviet space has evolved. The competition between Russia and the European Union for influence in these countries has become particularly pronounced, especially with the rise of various cooperative projects. The situation in Ukraine, beginning with Crimea's annexation and the conflict in the eastern regions in early 2014, marked a significant turning point in the geopolitical dynamics of the post-Soviet area. These events have reshaped the geopolitical landscape and introduced a new phase in Russia's foreign policy. The ongoing impact of these developments remains somewhat unclear, as the current stage of Russia’s foreign policy is still taking shape amidst continuing Western sanctions and evolving geopolitical strategies. The evolving nature of this stage underscores the complexity of Russia's foreign relations and the broader implications for the region.